Hierarchical Core/Shell Structured Ag@Ni(OH)2 Nanospheres as Binder-Free Electrodes for High Performance Supercapacitors - Sa Lv; Xuefeng Chu; Fan Yang; Huan Wang; Jia Yang; Yaodan Chi; Xiaotian Yang (Crystals, 2019)
Hierarchical Ag@Ni(OH)2 nanospheres were achieved directly on copper foam substrate through a convenient two-step process. Ag nanoflowers were formed on copper substrate by galvanic replacement technology between AgNO3 and copper foam followed by electrodeposition of a layer of Ni(OH)2. Ag nanostructures as cores not only dominated the final morphology of the composites, but also improved the electrical conductivity, increased the specific surface area of the active electrode material, and even directly participated in the electrochemical reactions. The resulted Ag@Ni(OH)2 nanospheres could be directly used as high-performance binder-free electrodes and exhibited enhanced electrochemical performance with a high specific capacitance of 1.864 F cm−2 and long cycling lifespans of 90.43% capacity retaining after 3000 cycles.